Using AI to Build from Text to Video for Tourism Marketing - Zolanski, Amanda; Borcea, Razvan (CV TOPAZART, 2024)
This article delves into the fascinating realm of utilizing artificial intelligence (AI) to bridge the gap between textual content and video creation. With the exponential growth of digital content, the demand for engaging and dynamic videos has never been higher. AI technologies offer innovative solutions to streamline the process of transforming textual information into captivating video content. From natural language processing (NLP) algorithms that extract key themes and concepts to deep learning models that generate visuals and animations, AI empowers creators to efficiently produce compelling videos from text. This article explores the diverse applications of AI in text-to-video generation, highlighting its potential to revolutionize content creation workflows, enhance storytelling capabilities, and cater to diverse audience preferences. Through real-world examples and insights, it showcases how AI-driven approaches are reshaping the landscape of multimedia content production, opening up new avenues for creativity and expression.